Analysis of the Impact of Profitability on Stock Returns for Banking Companies Listed on the Indonesia Stock Exchange, 2020–2024 - Alifiana, Metania Lestari; Adriani, Ade; Yuliani, Rahma (Dinasti Publisher, 2026)
This study aims to analyze the effect of profitability ratios on stock returns for banking companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. The independent variables used are Return on Assets (ROA), Return on Equity (ROE), Gross Profit Margin (GPM), Operating Profit Margin (OPM), and Net Profit Margin (NPM), while the dependent variable is stock returns. The research method used is a quantitative approach with multiple linear regression analysis. The results indicate that, collectively, all five profitability ratios significantly influence stock returns (R² = 0.710). Individually, ROE, GPM, and NPM have a significant positive effect, while ROA and OPM do not have a significant effect. NPM is the most dominant variable influencing stock returns. These findings indicate that profitability, particularly net profit and return on equity, is a key factor in attracting investor interest in the banking sector.